The lymphocyte-to-monocyte ratio may distinguish complicated from non-complicated pediatric appendicitis: A retrospective study and literature review - Matthias Nissen; Ralf-Bodo Tröbs (Elsevier, 2022)
Background: To date, no parameter with satisfactory accuracy exists for the diagnosis of appendicitis. This retrospective study describes the discriminatory value of preoperative hematologic factors associated with complicated and non-complicated pediatric appendicitis. Methods: Clinical and laboratory data were obtained from 294 children diagnosed with appendicitis on admission and treated at our tertiary-level pediatric hospital from 2015 to 2017; they were divided into three groups: control group (n = 118), histologically proven complicated (n = 120), and non-complicated (n = 56) appendicitis. Results: Complicated appendicitis was associated with male preponderance and elevated neutrophil and monocyte levels (all p < 0.001). Non-complicated appendicitis was associated with elevated eosinophil levels (p = 0.023), and unaltered lymphocyte levels (p = 0.30). Compared to non-complicated disease, the lymphocyte-to-monocyte ratio (LMR) was decreased in complicated appendicitis (p = 0.003) but unaltered in the control group (p = 0.38). In the discrimination analysis, LMR had high accuracy (AUC 0.73 ± 0.05; p < 0.001; odds ratio (OR) (95% confidence interval (CI)) 6.0 (2.4-15.3)) and was the only parameter independently associated with complicated appendicitis on regression analysis (OR (95% CI), 0.544 (0.359-0.825); p = 0.004). Conclusion: We identified LMR as a novel potential marker for the differentiation of complicated from non-complicated pediatric appendicitis. This has implications on the treatment approach, either surgical in complicated disease or conservative in non-complicated disease.